2024
DOI: 10.1101/2024.05.27.596013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The threePlasmodium falciparumAurora-related kinases display distinct temporal and spatial associations with mitotic structures in asexual blood stage parasites and gametocytes

Matthias Wyss,
Basil T. Thommen,
Jacob Kofler
et al.

Abstract: Aurora kinases are crucial regulators of mitotic cell cycle progression in eukaryotes. The protozoan malaria parasite Plasmodium falciparum replicates via schizogony, a specialised mode of cell division characterized by consecutive asynchronous rounds of nuclear division by closed mitosis followed by a single cytokinesis event producing dozens of daughter cells. P. falciparum encodes three Aurora-related kinases (PfARKs) that have been reported essential for parasite proliferation, but their roles in regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…5B). To provide an unbiased quantification, we integrated the signal intensities originating from PfSET10-mNG and Pfg377 labeling using ImageJ as described previously 56 . This analysis revealed that PfSET10-mNG was only expressed in gametocytes that also displayed strong Pfg377 signal intensities, indicating that in late stage gametocytes PfSET10 is indeed only expressed in females (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B). To provide an unbiased quantification, we integrated the signal intensities originating from PfSET10-mNG and Pfg377 labeling using ImageJ as described previously 56 . This analysis revealed that PfSET10-mNG was only expressed in gametocytes that also displayed strong Pfg377 signal intensities, indicating that in late stage gametocytes PfSET10 is indeed only expressed in females (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the sex-specific expression of PfSET10-mNG in stage V gametocytes (day 13), IFAs α-mNeonGreen and α-Pfg377 antibodies and DAPI were performed on methanol/acetone-fixed thin blood smears. Image acquisition with the 40x objective was followed by automated quantification of the fluorophore signal intensities emitted from the secondary antibodies (Alexa Fluor 488-conjugated α-mouse IgG, Alexa Fluor 568-conjugated α-rabbit IgG) and DAPI using a Fiji macro (ImageJ version 1.52n) as described previously 56 . In brief, images were segmented based on the Pfg377 signal using the auto-threshold “Triangle”, which identified potential male and female gametocytes.…”
Section: Methodsmentioning
confidence: 99%